The Influence of The PjBL Model Based on Local Gorontalo Cultural Values to The Learning Outcomes in Simple Aircraft Concepts - Dewa Gede Eka Setiawan; Nur Rahma Kuengo; Supartin Supartin; Asri Arbie; Dewi Diana Paramata; Nova Elysia Ntobuo (Postgraduate, University of Mataram, 2024)
This research aims to determine the influence of the Project Based Learning (PjBL) model based on local Gorontalo cultural values ​​on the learning outcomes of simple aircraft concepts. This research is experimental, with the research design being a one-group pretest-posttest design. The population in this study was all class VIII of SMP Negeri 8 Paguyaman for the 2023/2024 academic year. Research data was collected using test techniques. Then, the data was analyzed using descriptive and inferential statistics, including normality tests, hypothesis tests, and n-gain analysis. The average score for all sample classes for class VIII students is greater than the minimum completion criteria (MCC), as shown by the average score for the experimental class of 81.97, replication class 1 of 80.91, and replication class 2 of 80.15, compared to the MCC of 75. Based on the course results, the average normalized gain obtained by the experimental class was 0.69, replication class 1 was 0.68, and replication class 2 was 0.68, meaning that all sample classes are in the medium category. Thus, the PjBL model based on local Gorontalo cultural values ​​has a significant effect on student learning outcomes in simple aircraft concepts